An investigation of the equivalence between combline and evanescent-mode waveguide filters & of aspects related to reduction of manufacturing costs for combline filters - Nassar, Shamim O. (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScEng)--Stellenbosch University, 2011.